Regional anesthesia for pain control in children with solid tumors—a review of case reports - Baizhanova, Aliya; Zhailauova, Azhar; Sazonov, Vitaliy (Frontiers in Pediatrics, 2024)
Around seventy percent of all childhood cancer patients suffer from severe pain. This pain can arise from various sources, including tumors themselves, pain caused by metastasizing tumor cells or as the outcome of therapy meant to deal with tumors.If managed inadequately, such pain can lead to many hazardous sequelae. However, there are extreme cases when pain does not respond to standard treatment. For such cases, regional anesthesia or nerve blocks are utilized as the utmost pain control measure. Blocks are used to treat pain in patients who no longer respond to conventional opioid-based treatment or whose worsened condition makes it impossible to receive any other therapy. The data regarding the use of regional anesthesia for such cases in the children population is limited. This review of case reports discusses the regional anesthesia techniques used in pediatric patients with solid tumors. It was concluded that nerve blocks, although rarely performed, are a safe and efficient way of pain control in children with solid tumors. The major settings for block performance are postoperative pain control and palliative care. We observed that block indication and its outcomes depend on unique health circumstances in which they should be performed. Patients with similar diagnoses had differing outcomes while receiving the same block treatment.